Nipple adenoma detected by multimodal ultrasound: a case report and literature review - Zhang, Jingwen; Wu, Tingting; Ma, Yuqin (Frontiers in Oncology, 2024)
Nipple adenoma (NA) is a rare benign lesion of the lactiferous ducts, often mistaken for malignancy due to its diverse clinical and imaging presentations. We report the case of a 34-year-old female presenting with persistent bloody discharge and nipple erosion, for which multimodal ultrasound evaluation was pivotal in the differential diagnosis. Ultrasonography revealed a hypoechoic, well-defined nodule in the left nipple, with significant blood flow and a fast-in-fast-out contrast enhancement pattern, indicative of NA. Despite the presentation mimicking malignant processes, the benign nature of the lesion was confirmed postoperatively via histology and immunohistochemistry. This case underscores the value of a comprehensive ultrasound approach in diagnosing NA, emphasizing its ability to distinguish it from malignant lesions, and thus infer an appropriate treatment course. Maintaining a high index of suspicion coupled with tailored ultrasound techniques is recommended for accurate NA diagnosis, which remains a challenging yet critical task to avoid unnecessary aggressive interventions.